Corticosteroids in patients with vestibular neuritis: An updated meta-analysis - Bogdanova, Anna; Dlugaiczyk, Julia; Heckmann, Josef Georg; Schwab, Stefan (Acta Neurologica Scandinavica, 2022)
Vestibular neuritis is a common neuro-otological entity. Therapeutically, corticosteroids are advised, although the evidence is limited. The objective of this review is to update meta-analyses of clinical trials that address the question of whether patients with vestibular neuritis treated with corticosteroids show better recovery than control patients. The electronic databases Medline, Scopus and Cochrane were searched for clinical trials for the years 1970-2020 without language restriction. Data were extracted, and outcome parameters were subjected to conventional and cumulative meta-analysis using a commercially available software program (). Finally, 15 trials with 363 participants in the treatment and 489 in the control groups were identified and could be included. Eight studies were judged to be at high risk of bias. The odds ratio (OR) for good outcome in the acute phase was 3.1 (95% CI 1.2-7.8; p = .015) in favour of steroid treatment leading to the number needed to treat (NNT) = 6 (95% CI 4-23). The odds ratio (OR) for restoration of vestibular function in the follow-up was 2.4 (95% CI 1.3-4.4; p = .004) for the benefit of steroid treatment resulting in a NNT = 7 (95% CI 5-18). The results of the cumulative statistics did not differ. The risk of adverse effects was higher in patients treated with steroids with an OR of 10.9 (95% CI 1.3-93.8; p = .015) and an estimated number needed to harm (NNH) = 4 (95% CI 3-19). The advantage for corticosteroids remained when differentiating between patients who participated in randomized or non-randomized clinical trials. Steroid treatment in vestibular neuritis resulted in a statistically significant benefit compared to control therapies. However, broad heterogeneity of the studies, mostly low-grade quality of studies, high risk of bias and broad confidence intervals put the findings into perspective allowing only a careful judgement of some benefit of corticosteroids. The findings, however, support the call for an adequately powered and well-designed randomized controlled trial to re-evaluate the effectiveness of corticosteroids.
CRIS-Team WoS Importer:2022-09-09